Longitudinal Course and Correlates of Parents’ Differential Treatment of Siblings in Mexican-Origin Families - Padilla, Jenny (Fam Process, 2017)
Parents’ differential treatment (PDT) is a common family dynamic that has been linked to youth development and well-being, including adjustment problems and poor sibling relationships. Much less is known, however, about the developmental course of PDT and the conditions under which parents treat their children differently in adolescence and young adulthood. This study examined longitudinal changes in mothers’ and fathers’ differential warmth and conflict with their two offspring from early adolescence through young adulthood, and examined parents’ experiences of individual stress (depressive symptoms and role overload) and marital difficulties as time-varying correlates of (changes in) parents’ differential treatment. We also tested crossover effects to determine whether mothers’ experiences of individual stress and marital difficulties were linked to fathers’ differential treatment, and vice versa. Participants were mothers, fathers, and two siblings from 246 Mexican-origin families who were interviewed in their homes on three occasions over eight years. Multilevel models revealed that mothers’ and fathers’ differential conflict with their two children increased until middle adolescence and then declined into young adulthood, but there were no changes over time for parents’ differential warmth. In general, both mothers’ and fathers’ levels of differential treatment were exacerbated by their own experiences of individual stress and marital difficulties and also by the experiences of their spouses. However, in some cases, greater stress than usual was linked to less differential treatment than usual.